Twofold symmetry of c-axis resistivity in topological kagome superconductor CsV3Sb5 with in-plane rotating magnetic field - Ying Xiang (Nature Portfolio, 2021)
The recently discovered class of kagome metals AV3Sb5, where A stands for K, Rb, Cs, has been shown to host a variety of exotic phases. Here, the authors report the two-fold rotational symmetry of superconductivity and signatures of an in-plane nematic electronic state in CsV3Sb5 under in-plane magnetic field.